CULTURAL DIVERSITY IN ENGLISH-SPEAKING COUNTRIES - Khalilova Shokhista Mukhammadi qizi; Rashidova Gulchekhra Olimjon qizi (TADQIQOTLAR, 2026)
Abstract This article analyzes cultural diversity in English-speaking countries from historical, sociolinguistic, and intercultural perspectives. The research examines multiculturalism, national traditions, educational systems, and cultural interaction in countries such as the United States, the United Kingdom, Canada, Australia, and New Zealand. The study highlights the importance of intercultural communication and linguistic diversity in the modern globalized world.